Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\log_b (1 - 3x) = 3 + \log_b x$$

If I use the properties of logs, I end up with

$$\log_b \left(\frac{1 - 3x}{x}\right) = 3$$

From there, the example I have says to exponentiate both sides, however, they use a $\log_2(\text{equation}) = 2$. They then raise both sides to the $2$. I can't seem to do this here, does someone have an example that better fits my situation?

share|cite|improve this question
Raise $b$ to the powers involved. Note that $b^{\log_b(y)}=y$. So you should end up with $\frac{1-3x}{x}=b^3$. – André Nicolas Dec 6 '11 at 20:16
I've got it solved, thanks. If you answer this question with your comment, I'll mark this as the accepted answer. – erimar77 Dec 6 '11 at 20:31
It seems what is really missing here is an understanding of logarithms: Recall that $$\log_b(z) = y \quad\iff\quad b^y = z.$$ In other words, $\log_b(z)$ is the power to which you exponentiate $b$ to get $z$. In your case, $$\log_b\left( \frac{1-3x}{x} \right) = 3 \quad\iff\quad b^3 = \frac{1-3x}{x}.$$ – JavaMan Dec 6 '11 at 20:58
up vote 1 down vote accepted

Remember, any $\log$ to the base $b$, such as $\log_b(y)$, is in its heart an exponent. Let us start, then, from your expression $$\log_b\left(\frac{1-3x}{x}\right)=3.$$ Raise $b$ to the powers we see on each side. We get $$b^{\log_b\left(\frac{1-3x}{x}\right)}=b^3.$$ The left-hand side simplifies greatly. We get $$\frac{1-3x}{x}=b^3.$$ The rest is elementary algebra. The above equation is (for $x\ne 0$) equivalent to $$1-3x=b^3 x,$$ which is an easily solved linear equation.

Comment: There was no need to do the preliminary manipulation. We are told that $$\log_b(1-3x)=3+\log_b x.$$ Raise $b$ to the power on the left-hand side, the right-hand side. We obtain $$b^{\log_b(1-3x)}=b^{3+\log_b x}.$$ By the "laws of logarithms" this yields $$1-3x=b^3 x.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.